Peran sistem informasi manajemen di dalam mengendalikan operasional badan usaha milik daerah - Lesi Hertati; Asmawati Asmawati; Marlina Widiyanti (Insight Management Journal, 2021)
Management information system is an information system derived from integrated sub-systems and provides information to management for decision making. Management information systems are needed to help the company's business activities run well. As technology develops, companies need a system that can control and manage information with both accurate and timeline. The purpose of management information systems is very important to help internal and internal company activities in requiring human resources who have skills and abilities. The system contains a set of data processes that can be processed, analyzed and displayed so that the data becomes useful for the needs of making a decision called a management information system. Management information systems are very useful tools to support and control the operations of regionally owned enterprises. The main purpose of a management information system is to collect and organize all data from different levels of regional owned enterprises, for decision making to increase the productivity and profitability of computer-based local-owned enterprises and can be in the form of excel sheets or more complex platforms. In addition, data can be accessed and processed internally and externally. Thus, the information system used is more efficient and productive. This research was conducted on 132 related sub-units of regional-owned enterprises using descriptive and explanatory uses, while for sampling using the SEM Lisrel cluster technique. The results of this study indicate that human resource competence, job performance, job promotion, have an effect on the role of management information systems